PENGGUNAAN MEDIA PEMBELAJARAN SPARKOL VIDEOSCRIBE TERHADAP MOTIVASI BELAJAR SISWA DI SMP NEGERI 2 SUNGGUMINASA KABUPATEN GOWA - Husain Al Hidayah; Andi Adam; Nurindah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The low motivation of students to learn in cultural arts subjects is due to the lack of learning media applied by teachers in class. This results in students being less enthusiastic about participating in class learning. This is clearly seen when the teacher gives questions or questions to students, most students are unable to answer questions from the teacher. The learning media used is still watching which only uses learning media such as whiteboards and printed books. So that it makes students feel bored in receiving learning. then the goal to be achieved in this study is to determine the effect of using Sparkol Videoscribe media on student learning motivation at SMP Negeri 2 Sungguminasa, Gowa Regency. The type of research used in this study is a type of quantitative research experimental approach with pre-experiment method using one shot case study research design. Based on the results of the research and discussion that has been stated, it can be concluded that there is an effect of using Sparkol Videoscribe learning media on the motivation to learn cultural arts of seventh grade students at SMP Negeri 2 Sungguminasa, Gowa Regency. This shows that through hypothesis testing as evidenced by statistical analysis of the correlation test which states that the sig value ≥ α, namely 0.041 ≥ 0.05. Thus H1 is accepted and H0 is rejected.